A case of bullous pemphigoid after a long‐term administration of anti‐PD‐1 antibodies in a patient with non‐small‐cell lung cancer. Issue 6 (20th June 2021) - Yokoyama, Emi; Yamasaki, Osamu; Kubo, Toshio; Koga, Hiroshi; Ishii, Norito; Morizane, Shin
Abstract : We described a case of BP that developed 2.5 years after the administration of nivolumab for metastatic non‐small cell lung cancer. Our report highlights the fact that dermatologists should be aware of anti PD‐1‐related BP, which can appear very late during treatment.